2005
DOI: 10.1021/jp0460339
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Water, Methanol, and Acetonitrile on Solvent Relaxation and Rotational Relaxation of Coumarin 153 in Neat 1-Hexyl-3-methylimidazolium Hexafluorophosphate

Abstract: The dynamics of solvent relaxation in ionic liquid (IL)-water, IL-methanol, and IL-acetonitrile mixtures have been investigated using steady state and picosecond time-resolved fluorescence spectroscopy. We have used Coumarin 153 (C-153) and 1-hexyl-3-methylimidazolium hexafluorophosphate ([hmim][PF(6)]) as fluorescence probe and IL, respectively. The steady-state emission spectra showed that the gradual addition of cosolvents increases the polarity of the mixtures. In neat [hmim][PF(6)] and all IL-cosolvent mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
139
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(145 citation statements)
references
References 57 publications
6
139
0
Order By: Relevance
“…C153 is considered to be an ideal probe because the dynamics probed by C153 have been found to be primarily related to nonspecific solute−solvent interactions in many RTIL systems. 17,52,53,58 BPP is a particularly sensitive probe of microviscosity especially in the heterogeneous environment such as ionic liquid systems. 55−57,59−62 As a result, the microviscosity enhancement effects in the [bmim] [PF 6 ] and TEGDME hybrid system were observed by probing the microviscosity through the two complementary experimental methods.…”
Section: Introductionmentioning
confidence: 99%
“…C153 is considered to be an ideal probe because the dynamics probed by C153 have been found to be primarily related to nonspecific solute−solvent interactions in many RTIL systems. 17,52,53,58 BPP is a particularly sensitive probe of microviscosity especially in the heterogeneous environment such as ionic liquid systems. 55−57,59−62 As a result, the microviscosity enhancement effects in the [bmim] [PF 6 ] and TEGDME hybrid system were observed by probing the microviscosity through the two complementary experimental methods.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, solute-solvent interactions can affect the probesolvent interactions. [21] Preferential solvation may arise whenever the bulk mole fraction solvent composition is different from the solvation microsphere solvent composition. The response of the spectroscopic probe is dependent on the composition in the solvation microsphere, and therefore it is able to measure the eventual preferential solvation phenomena occurring in the solvent mixtures.…”
Section: Introductionmentioning
confidence: 99%
“…[14][15][16][17][18][19] The findings of these investigations reveal that solute rotation is sluggish compared to that in conventional solvents and the observed slow reorientation times have been ascribed to the high viscosity of the ionic liquids. Baker et al 14 have measured the reorientation times of a large non-polar solute BTBP (N,N-bis(2,5-di-tert-butylphenyl)-3,4,9,10-perylenedicaboximide) in ionic liquid 1-butyl-3-methylimidazolium hexafluorophosphate ([bmim + ][PF -6 ]) as a function of temperature and concluded that a single layer of [bmim + ] or ] associates with the solute.…”
Section: Introductionmentioning
confidence: 92%
“…Rotational diffusion and solvation dynamics has been investigated in mixtures of ionic liquid with polar solvents such as water, methanol and acetonitrile. 18,19,29 These studies reveal that solvation as well as rotational dynamics becomes faster with an increase in the amount of polar solvent which has been attributed to decrease in the viscosity of the ionic liquid. Addition of non-polar solvents such as toluene and 1,4-dioxane has been found to produce a similar effect on the dynamics.…”
Section: Introductionmentioning
confidence: 93%